ҚАРАҚАЛПАҚ ТИЛИНДЕГИ ПЕРИФРАЗАЛАРДЫҢ ТЕМАТИКАЛЫҚ ТОПАРЛАРЫ - Пирниязова, А.К.; Каллибекова, Г.П. (SCIENCE and SOCIETY, 2024)
The article is devoted to one of the figurative and expressive means - periphrases, used in the Karakalpak language. Periphrases of the language of poetry and journalism are analyzed and divided into thematic groups.
Keywords: karakalpak linguistics; periphrasis; journalistic style; visual and expressive means; poetry; thematic groups